2017
DOI: 10.1259/dmfr.20160188
|View full text |Cite
|
Sign up to set email alerts
|

Definition, classification and retrospective analysis of photostimulable phosphor image artefacts and errors in intraoral dental radiography

Abstract: Objectives: To detect and determine image error and artefact types in intraoral radiographs obtained with photostimulable phosphor (PSP) technology, place them in an appropriate classification and retrospectively analyze the PSP-specific image errors and artefacts. The causes and solutions of PSP-specific errors and artefacts have also been discussed. Methods: The radiographic database of Ondokuz Mayis University, Faculty of Dentistry, Department of Dentomaxillofacial Radiology, was used for this study. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…This study found no conveyor belt peeling3 or tongue artifacts,7 excessive cleaning of the plate surface artifacts,89 incorrect settings of processing menus,10communication error artifacts,11 or data cable malfunctions,11 but these artifacts were included in our classification because they had been defined in previous studies and reports.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…This study found no conveyor belt peeling3 or tongue artifacts,7 excessive cleaning of the plate surface artifacts,89 incorrect settings of processing menus,10communication error artifacts,11 or data cable malfunctions,11 but these artifacts were included in our classification because they had been defined in previous studies and reports.…”
Section: Resultsmentioning
confidence: 79%
“…3, 4, 5, 6). In this study, errors related to the scanner were identified with the help of our technical support team and previous studies 346891011…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations